Peran Modal Sosial dalam Pengembangan Masyarakat Desa Wisata Pujon Kidul Malang - Maarif, Usman (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2023)
THE ROLE OF SOCIAL CAPITAL IN SOCIETY DEVELOPMENT TOURISM VILLAGE OF PUJON KIDUL MALANG. The empowerment of the Pujon Kidul tourism village community has succeeded in making Pujon Kidul village, which was originally a poor village, into a developed and independent tourism village. At this time the village of Pujon Kidul has become one of the best tourist villages in Indonesia. At present the Pujon Kidul tourism village business units have made a very large contribution to the village's original income. One of the factors that has a big role in the success of community empowerment programs in the village of Pujon Kidul is the role of social capital in the community. Therefore, this article focuses on the role of social capital in community empowerment in Pujon Kidul Village, Malang Regency. The method used in this study is qualitative literature. The results of the study show that social capital has many roles in community empowerment activities in the village of Pujon Kidul. Elements of social capital systemically support the achievement of community empowerment goals. The social capital that exists in the Pujon Kidul village community has encouraged the formation of social relations and has become the energy that facilitates and accelerates the implementation of community empowerment programs in the Pujon Kidul village.